أثر توافق السيولة في ظل التضخم على الأزمات المالية: دراسة ميدانية على المصارف العامة بولاية الخرطوم - إبراهيم، الهادي آدم محمد; آدم، عبدالسلام عوض خير السيد (جامعة النيلين - كلية التجارة, 2016)
The study problem is represented in a lack of understanding to the importance of the availability of liquidity in banks during inflation and its role in reducing incidence of financial crisis. The study aimed basically to know the concept of bank liquidity, its importance and its role in reducing financial crises when during inflation. The study adopted inductive approach, and descriptive analytical approach, and questionnaire was used in collecting data from some of Sudanese banks that works in Khartoum State The study found that the availability of liquidity during inflation enables customers to fulfill their obligations towards banks and reduces credit risks, and unavailability of enough amount of liquidity indicates a lack of bank's financial position integrity which in turn predicates possible occurrence of banks' financial crises. The study recommended banks to take the financial and administrative procedure that enables them to attract largest amount of investment deposits for providing more liquidity and limits financial crisis.
تمثلت مشكلة الدراسة في عدم الإدراك لأهمية توافر السيولة لدي المصارف في بيئة التضخم والدور الذي تلعبه في الحد من حدوث الأزمة المالية. هدفت الدراسة بصورة أساسية إلى معرفة مفهوم السيولة المصرفية وأهميتها ودورها في الحد من الأزمة المالية حال توافرها في ظروف التضخم. اعتمدت الدراسة على المنهج الاستقرائي والمنهج الوصفي التحليلي، واستخدمت استمارة الاستبانة لجمع البيانات من بعض المصارف، العاملة بولاية الخرطوم. توصلت الدراسة إلى أن توافر السيولة في ظروف التضخم يمكن العملاء من الوفاء بالتزاماتهم تجاه المصارف ويقلل من المخاطرة الائتمانية وأن عدم توافر قدر كاف من السيولة يعد مؤشرا على عدم سلامة المركز المالي للمصرف مما ينبئ بحدوث الأزمات المالية للمصارف أوصت الدراسة بآن تتخذ المصارف من التدابير المالية والإدارية ما يمكنها من جذب أكبر قدر من الودائع الاستثمارية لتوفير والسيولة والحد من الأزمات المالية.
Keywords: الخرطوم -- إدارة البنوك -- السياسة النقدية -- الأزمات المالية